Edoardo Esposito, Con altra voce. La traduzione letteraria tra le due guerre (Altre Modernità, 2020)
Edoardo Esposito, Con altra voce. La traduzione letteraria tra le due guerre(Roma, Donzelli, 2018, pp. 169 ISBN 978-88-6843-869-2)di Paolo Caponi